Analysis of Chemical and Physical Soil Fertility on Maize (Zea mays L.) Cultivated Land in Telaga Biru District, Gorontalo Regency, Indonesia - Rahman, Adriyanto; Ilahude, Zulzain; Arsyad, Silviana; Nurmi; Rahman, Rival (International journal of technology and education research, 2026)
Maize (Zea mays L.) is a significant food commodity in Telaga Biru Subdistrict, Gorontalo Regency; therefore, information on soil fertility is crucial as a basis for effective land management. This study aims to analyze the chemical and physical fertility of soils in maize cultivation areas and to identify efforts to improve maize productivity in Telaga Biru Subdistrict. The study was conducted from April to November 2025 in Telaga Biru Subdistrict, Gorontalo Regency. A descriptive quantitative method with a land unit-based survey approach was employed. Soil sampling was conducted diagonally in three villages: Timuato, Modelidu, and Talumelito, at a depth of 0-20 cm. The analyzed chemical fertility parameters included soil pH, nitrogen, organic carbon, cation exchange capacity, available phosphorus, potassium, and base saturation. Physical soil properties analyzed included soil texture, bulk density, and soil color. The findings showed that the soil pH was slightly acidic, with nitrogen and organic carbon contents falling into the low to moderate categories. The cation exchange capacity and the availability of phosphorus and potassium were moderate, while base saturation was relatively low: The physical soil properties were dominated by clay to clay loam textures with relatively high bulk density values. These conditions indicate that maize cultivation land in Telaga Biru Subdistrict has sufficient fertility to support plant growth; however, appropriate soil management is still required through balanced fertilization, the addition of organic matter, and improvement of soil physical properties to enhance productivity sustainably.